2010
DOI: 10.5751/ace-00358-050101
|View full text |Cite
|
Sign up to set email alerts
|

Vesper Sparrows and Western Meadowlarks Show a Mixed Response to Cattle Grazing in the Intermountain Region of British Columbia

Abstract: Green. 2010. Vesper sparrows and western meadowlarks show a mixed response to cattle grazing in the intermountain region of British Columbia. Avian Conservation and Ecology -Écologie et conservation des oiseaux 5(1): ABSTRACT. Livestock grazing in the shortgrass steppe of the Intermountain region of British Columbia is predicted to have significant effects on grassland habitats and their associated ground-nesting bird communities. We tested whether grazed and ungrazed sites could be discriminated on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Birds breeding in native mixedgrass prairie evolved with the disturbance created by grazing bison (Bison bison) and wildfire (Knopf and Samson 1997;Askins 2000), and there is some evidence suggesting that cattle may fulfill some of the ecological functions historically filled by bison (Hart 2001;). Both bison and cattle grazing may increase plant species diversity (Hart 2001;Towne et al 2005) and heterogeneity of vegetation (Knapp et al 1999;Derner and Whitman 2009;Harrison et al 2010) relative to that in ungrazed prairie. Prairie songbird communities have a wide range of habitat requirements, and a heterogeneous vegetation structure can provide varied microhabitats suitable for a range of different species (Knopf 1996;Madden et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Birds breeding in native mixedgrass prairie evolved with the disturbance created by grazing bison (Bison bison) and wildfire (Knopf and Samson 1997;Askins 2000), and there is some evidence suggesting that cattle may fulfill some of the ecological functions historically filled by bison (Hart 2001;). Both bison and cattle grazing may increase plant species diversity (Hart 2001;Towne et al 2005) and heterogeneity of vegetation (Knapp et al 1999;Derner and Whitman 2009;Harrison et al 2010) relative to that in ungrazed prairie. Prairie songbird communities have a wide range of habitat requirements, and a heterogeneous vegetation structure can provide varied microhabitats suitable for a range of different species (Knopf 1996;Madden et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Immediately after determining the fate of a nest, we measured 11 environmental variables, including altitude, nest-site habitat, nest location and human disturbance (Table 2). Grazing-disturbancerelated variables (Harrison et al 2010(Harrison et al , 2011 were measured within a 5-m radius centerd on a nest tree (Larison et al 1998, Martin 1998). …”
Section: Data Collectionmentioning
confidence: 99%
“…Effects of livestock grazing can vary regionally to the extent that some species select, avoid, or are neutral to grazing, depending on local conditions (Bock et al 1993). The pastures and haylands of New York State (Norment et al 2010) and the intermountain semidesert region of British Columbia (Harrison et al 2010) differ from the Great Plains, where much of what is known about effects of livestock grazing on birds in North America originates. Nevertheless, Harrison et al (2010) and Norment et al (2010) concluded that livestock management is compatible with the conservation of a number of grassland bird species, consistent with many studies from the Northern Great Plains (e.g., Bareiss et al 1986, Kruse and Bowen 1996, Koper and Schmiegelow 2007.…”
mentioning
confidence: 99%
“…From a management perspective, the conclusions are enlightening and frustrating; if the management objective is to minimize risk to birds from anthropogenic activity throughout the breeding season, more detailed understanding of how birds respond to local environments may be required to develop robust recommendations appropriate at local spatial and short temporal scales. Norment et al (2010) and Harrison et al (2010) both addressed the effects of a common, but surprisingly understudied, agricultural activity, livestock grazing, and did so in unique habitats. Effects of livestock grazing can vary regionally to the extent that some species select, avoid, or are neutral to grazing, depending on local conditions (Bock et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation